Drying process of black pepper in a swirling fluidized bed dryer using experimental method - Nur Fatihah, Mohd Roslan; Ahmmad Shukrie, Md Yudin (IOP Publishing, 2020)
Black pepper (piper nigrum) is one of the well-known spices extensively used worldwide. Drying is the most popular methods of preserving the black pepper. Unfortunately, this operation may negatively influence product quality. Moreover, due to the high heat capacity of water, drying is usually a long-lasting and energy-intensive process, thus new drying techniques are continuously being sought. Fluidized bed dryers have been applied to dry raw materials due to the advantages of good mixing efficiency and high heat and mass transfer rate. In order to control and optimize the drying process of fluidized bed dryers, it is necessary to develop reliable methods to measure the moisture content of solid particles in the bed. For this project we dried the black pepper using two methods which is drying under sun drying and swirling fluidized bed dryer using heater. The temperature for both drying will be the same. Then, the characteristic and the drying moisture ratio of the black pepper were compared between these two drying methods. The performance of the swirling fluidized bed dryer was evaluated based on the percentage of moisture content of loss reduction. The time taken for this drying is 10 hours, which considered as 1 day of drying process. The percentage of moisture content loss reduction is 57.9%. The moisture ratio after 10 hours of drying is 0.3420. In conclusion, drying using swirling fluidized bed dryer is the new technology that can be used in drying industry.